Energy aspects of urban last mile delivery - Letnik, Tomislav (JET on-line, 2018)
Cities are growing and, consequently, so is the need for a more efficient supply system to customers located in urban areas. Increasing traffic congestion is hindering the efficiency of deliveries in city centres, which also negatively influences the energy aspects of transport processes. This paper considers an efficient solution for optimizing urban freight deliveries and presents the results of a case study for a small historical city centre. A tool is based on optimal vehicle routing and the assignment of the most optimal loading bay. It results in considerable savings in travel time, travel distance, and energy.
Keywords: cestni transport; dostava; energetska učinkovitost; energy efficiency; last mile delivery; loading bays; mesta; optimizacija; optimization; transport